(untitled) (Annals of Medical Research, 2022)
Aim: To analyze the distribution of gene mutations in myeloid neoplasias, based on next generating sequencing technology (NGS) and evaluate their clinical implications and impact on the risk stratification. Materials and Methods: 67 bone marrow samples which belongs to 48 different patients who were diagnosed with myeloid neoplasia and tested with 30 gene myeloid panel by NGS in our center were evaluated retrospectively. Distribution of genomic alterations and clinical implications were compared in different groups. Results: Samples were separated into different groups according to the diagnostic categories. Most common diagnosis was acute myeloid leukemia (AML) with the rate of 58.3%. FLT3 mutation was the most common mutation in AML and whole population. After the incorporation of the NGS results into the prognostic classification in newly diagnosed AML group, 47.1% of the patients were up-staged or down-staged according to the European Leukemia Network (ELN) risk stratification system. Conclusion: Analyzing the mutation profiles with NGS in myeloid neoplasias has an important and remarkable effect on diagnosis and management of this group of diseases.